A STUDY OF CONSUMERIST BEHAVIOR IN ISLAM IN THE CONTEXT OF E-COMMERCE - Riska Zafirah; Hafiizh Maulana; Eka Octavian Pranata (Jurnal Dinamika Ekonomi Syariah, 2026)
The rapid advancement of digital technology has fueled the expansion of e-commerce and changes in consumer consumption patterns, particularly through double-date promotional events. Time-limited promotional strategies often trigger psychological pressure known as Fear of Missing Out (FoMO), which may influence impulsive behavior. This study aims to analyze the effect of double-date promotional events and FoMO on impulsive buying, as well as to examine the role of FoMO as a mediating variable. This study employed a quantitative explanatory method. Data were collected through an online survey of 130 Generation Z respondents in Banda Aceh, selected using purposive sampling techniques. The data were analyzed using path analysis with the Sobel test to examine the mediating effect. The findings indicate that double-date promotional events do not have a direct and significant effect on impulsive buying, whereas FoMO has a direct and significant effect on impulsive buying behavior. Furthermore, the analysis confirms that FoMO functions as a mediating variable; however, the mediating effect has not reached statistical significance. This suggests that impulsive buying behavior is more strongly influenced by psychological factors than by promotional strategies. From an Islamic perspective, these findings emphasize the importance of self-control in consumption activities in order to achieve maslahah and avoid excessive consumption.